Ethnic diversity and polarization in Vojvodina - Áron Léphaft; Ádám Németh; Péter Reményi (Hungarian Geographical Bulletin, 2014)
From a methodological perspective, this paper aims to demonstrate that ethnic diversity can be an objectively measurable notion, thus multi-ethnicity may have its own ‘units of measurement’. However, while the Hungarian geographic literature has concentrated by now on only the fragmentation (i.e. ‘Ethnic Diversity Index’), another type of diversity should be also defined: the phenomenon called polarization when two or maximum three ethnic groups with nearly equal population number are present. Using the so-called ‘ethnic polarization index’ our paper emphasizes that the increase or decrease of diversity cannot be described as a two-dimensional process. Thus in our case study of Vojvodina not only the homogenizing and diversifying territories are outlined, where the minorities are shrinking, and conversely where the minorities increase their rate at the expense of the majority. Since both homogenization and diversification can result in polarization, it does also matter, which way the balance will shift regarding polarization. Taking intonconsideration the broad scale of potential impacts of ethnic polarization on social, economic and political spheres (e.g. on the risk of conflicts), we find it important to underline that human geography and sociological research in the future should focus on the polarizing territories as well which have been defined in our study.